FEATURES OF CLINICAL MANIFESTATIONS, CELLULAR AND HUMORAL IMMUNITY OF NEWBORNS WITH INTRAUTERINE MIXED INFECTIONS - M.A. YUSUPOVA; K.I. ISMOILOV (Avicenna Tajik State Medical University, 2020)
Objective: To study the features of clinical manifestations, cellular and humoral immunity of newborns with intrauterine mixed infections (IUMI). Methods: A comprehensive survey of 45 infants with IUMI was carried out. Depending on the classification of IUMI they were divided into 3 main groups: group I - 24 patients (53%) with the viral-bacterial association, group II - 12 patients (27%) with the viral-viral association, and group III - 9 patients (20%) with the viral-parasitic association. The control group consisted of 10 newborns born from uninfected, somatically healthy mothers. Diagnosis of IUMI was based on the detection of specific antibodies of the IgA, IgG and IgM classes, as well as phagocytic activity and phagocytic index of leukocytes. In addition, general clinical, biochemical, bacteriological and instrumental research methods have been conducted. Results: The blood serum IgA and IgM indices in patients of the main group were significantly higher, and the mean IgG values were lower compared to the control group. Analysis of cellular immunity parameters in the main group showed a decrease in the number of mature T-lymphocytes (CD3), B-lymphocytes (CD20), the number of T-helpers and cells that produce IL-2 in the peripheral blood, compared with the control group. In the main group, there was also an increase in the number of apoptosis cells (CD95), cells with high cytotoxic activity (CD25, CD71) and the percentage of natural killer cells (CD16). A decrease in the phagocytic activity and phagocytic index of neutrophils was recorded, which indicates the insufficiency of the nonspecific component of immunity. Conclusion: In newborns, various changes were found both on the part of specific and nonspecific components of immunity. This indicates the development of secondary immunodeficiency in this category of patients and makes it necessary to add to the main treatment of immune corrective therapy.